New challenges of the german minority kindergarten teacher profession (Training and Practice : Journal of Educational Sciences, 2018)
At the beginning of the 90ies I graduated as a German minority kindergarten teacher from Sopron. Additional to my instructor work I keep playful German activities in a private education institute for small children above half year of age, but mainly for those of kindergarten age. During my researches in minority kindergartens I have detected a more significantly occurring problem: German minority kindergarten teacher training does not provide sufficient German minority kindergarten teachers and in several cases not on appropriate level and the major part of the graduates does not even start or leaves the job. The reason is apparently wide-ranging, but in many cases it can be explained by the lack of financial and ethical appreciation. Most of them come to the decision already during their university years to start their career in Austria or Germany. There have been several factors for a long time which made their intellectual identification insecure. Social perception is such a factor, which identifies this qualification with low prestige. In my discourse I attempt to introduce based on the example of my activity what possibilities are offered for keeping these teachers at home and spreading their domestic professional life. A phenomenon can be observed today that the parents would like to start the musical, movement, foreign language and other development of their children as soon as possible. They think through the education of their children they can alter the social position of their families. They would like their children to be successful grown-ups, for this reason they expect from them to acquire as much cultural capital as possible. They perceive well that education plays the most important role in the acquisition of cultural goods. The parents organize the life of their children to an extent never experienced. In my discourse I would like to demonstrate how we can organise foreign language activities for the smallest ones reacting to these parental demands.